Sport Nutrition Drinks Based on Octopus Protein Hydrolysate - Bambang Riyanto; Wini Trilaksani; Rika Lestari (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractSport nutrition drinks are well-known in escalating athlete’s performance and endurance. These product developed from whey protein hydrolysates and soybean protein hydrolysates have already been recognized, however expansion from marine product is comparatively rare. Octopus (Octopus cyanea) widely acknowledged containing taurine and rich in amino acids is potential to be developed as ingredient for sport nutrition drink. The aims of this study were to create and characterize sport nutrition drinks based on marine peptides through Octopus protein hydrolyzate. Octopus protein hydrolysate has 77.78±2.69% degree of hydrolysis and 751.02±10.63 mg / 100g taurine. Sports nutrition drinks with the addition of 4% Octopus protein hydrolyzate was acceptable sensory panelists, and the serving size of 600 ml contained taurine 726.06±0.82 mg and detected 17 types of amino acids.